FINANCIAL AVAILABILITY OF IN-HOME MEDICAL TREATMENT OF PATIENTS WITH ALZHEIMER'S DISEASE - Mariana Arnaoudova; Anna Todorova; Antoaneta Tsvetkova (Peytchinski Publishing, 2016)
Background: Alzheimer's disease (AD) is a progressive neurodegenerative disorder and presents a great burden for the person, family and society as a whole. Since 2012, in Bulgaria, AD is accepted as a disorder of a great socio-economic significance and the drugs for home treatment are included in the reimbursement list of the National Health Insurance Fund (NHIF). Objective: To trace the access to treatment of Alzheimer's in-home patients, as a result of generic substitution on the base of share distribution of the original and generic products. Methods: We collected data for the sales of pharmaceutical products (PP's), containing donepezil hydrochloride and memantine hydrochloride from a distributor for the Northeast region of Bulgaria (Varna) in the period 2014-2015. An analysis of the percentage share distribution of the original and generic products was conducted. Results: According to our results original product Aricept accounts for only 4%, while the market share for its generics is 96%. In this group the share to be paid from NHIF is 25%, the remaining 75% from the cost is paid by the patients. The original product Axura occupies 8% market share, the generics- 92%. In this group the share to be paid from NHIF is 50% for generics, while Axura was removed from the Positive reimbursement list. We comment the significant differences in the sale shares in several directions. Conclusion: The reduction of expenses, with the use of generics, would help more patients to receive an optimal treatment and the savings could be redirected for other costly treatments.